2010
DOI: 10.3102/0002831209353595
|View full text |Cite
|
Sign up to set email alerts
|

Can 1st-Year College Students Accurately Report Their Learning and Development?

Abstract: Many higher education studies use self-reported gains as indicators of college student learning and development. However, the evidence regarding the validity of these indicators is quite mixed. It is proposed that the temporal nature of the assessment-whether students are asked to report their current attributes or how their attributes have changed over time-best accounts for students' (in)ability to make accurate judgments. Using a longitudinal sample of over 3,000 first-year college students, this study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 49 publications
(93 reference statements)
3
112
0
Order By: Relevance
“…If this is the case, then grades as measures of learning outcome is only partly comparable across disciplines and professions. Similar arguments are also proposed by Bowman, (2010Bowman, ( , 2011 who argued that there is hardly any correlation between grades after one year of study and grades at the end of studies and self-reported learning outcomes at the end of study. The data indicates that there is an ambiguous relationship between self-reported learning outcomes and grades.…”
Section: The Validity Of and Relationship Between Measuressupporting
confidence: 49%
“…If this is the case, then grades as measures of learning outcome is only partly comparable across disciplines and professions. Similar arguments are also proposed by Bowman, (2010Bowman, ( , 2011 who argued that there is hardly any correlation between grades after one year of study and grades at the end of studies and self-reported learning outcomes at the end of study. The data indicates that there is an ambiguous relationship between self-reported learning outcomes and grades.…”
Section: The Validity Of and Relationship Between Measuressupporting
confidence: 49%
“…As we noted earlier, scholars suggest standardized measures of critical thinking are more psychometrically valid than self-reported estimates (Bowman, 2010;Pascarella, 2001). As such, previous research may simply be masking the chance influence of technology on cognitive growth (i.e., committing Type I error).…”
Section: Summary Discussion and Limitationsmentioning
confidence: 99%
“…Second, in contrast to nearly all of the research on the impact of technology on intellectual development, we also use a standardized instrument to measure critical thinking. Although it is sometimes practically necessary to use self-reported measures of intellectual development, standardized instruments that assess critical thinking are generally viewed as more psychometrically valid measures (Bowman, 2010;Pascarella, 2001;Pike, 1996). Third, in contrast to Flowers and his colleagues (2000), we explore somewhat different dimensions of cognitive development among a very different sample of undergraduates over four years of college.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the use of recall to describe behavior sometimes proves unreliable. Bowman (2010) describes how measurement error, social desirability, and the halo effect influence the validity of self-reported assessment data supplied by college students about their learning and development, in contrast to data about student gains that are acquired through longitudinal studies. Bowman (2010) identifies a low correspondence between longitudinal and self-reported gains, suggesting that self-reporting is generally unreliable-a phenomenon that may have affected the information I received from students about their own sense of participation in the community of practice.…”
Section: Limitationsmentioning
confidence: 99%
“…My analysis is largely based on a few students' responses; there is no guarantee that the students accurately assessed and/or reported their performance in the course (Bowman, 2010). Accordingly, the extent to which they are participating in the CoP of environmental sciences cannot be established with precision.…”
Section: Limitationsmentioning
confidence: 99%